SUB6 Subtilisin is Involved During the Initial Adhesion of Trichophyton benhamiae and T. mentagrophytes onto Reconstructed Human Epidermis - Émilie Faway; Wilfried Poirier; Tsuyoshi Yamada; Kiyotaka Ozawa; Michel Monod; Bernard Mignon; Yves Poumay (JID Innovations)
The growing incidence of dermatophytoses and the emergence of strains resistant to available antifungal agents raise the need for a better understanding of the virulence mechanisms of dermatophytes to identify new therapeutic targets. The proteases of the subtilisin family have previously been highlighted as potential virulence factors for dermatophytes, in particular the protease SUB6, which was first discovered to be an allergen capable of inducing immediate and delayed hypersensitivity skin reactions. Moreover, SUB6 expression and SUB6 protein production were detected during experimental and natural skin infections with several dermatophyte species. In this study, we specifically investigated the importance of SUB6 during Trichophyton benhamiae and T. mentagrophytes dermatophytosis in a reconstructed human epidermis model by comparing parental strains with genetically engineered ones deleted (ΔSUB6) or complemented for the SUB6-encoding gene. Thereby, a role for SUB6 has been identified in the initial steps of adhesion to the host epidermal surface. However, the ΔSUB6 strains were able to finally invade the reconstructed human epidermis, suggesting that SUB6 is a robust fungal marker of infection but not an essential virulence factor.